The Demand of Urban Consumers for Safe Pork in the Vietnamese Mekong Delta - Huynh Viet Khai; Tran Thi Thu Duyen; Huynh Thi Dan Xuan (Journal of Social and Development Sciences, 2018)
This study applied the contingent valuation method to analyze the consumers’ demand for the proposed safe pork. The data was collected by face-to-face interviewing 884 urban households in the Vietnamese Mekong Delta. The results revealed that the majority of consumers (about 64%) paid attention to the proposed safe pork. Their willingness to pay was about VND 176,000 ($ 7.65) per kg, nearly double compared to the market price of conventional pork. The results showed that the respondents who had higher household income, larger proportion of elderly and children in the family, paid higher price of a conventional pork, and get more knowledge score on the safe pork are more likely, while the respondents who have more number of family members are less likely to pay for the proposed safe pork.